(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Permanent Magnet Synchronous Motors (PMSMs) are widely used in electric vehicle applications due to their high efficiency, compact size, and superior performance. However, their reliability is affected by electrical and thermal stresses, which can lead to both external and internal faults. Conventional protection methods primarily address external faults such as overcurrent, overvoltage, and overheating, but they are not effective in detecting internal issues such as gradual demagnetization of rotor magnets. This work proposes a PMSM drive system with integrated safety and monitoring features to enhance operational reliability. The system employs Field Oriented Control (FOC) for precise control of torque and speed while continuously monitoring key parameters such as stator current, voltage, and temperature. In addition to standard protection mechanisms, a sensorless demagnetization detection method is incorporated using variations in electrical signals, eliminating the need for additional hardware sensors. Based on the detected level of demagnetization, appropriate control actions are implemented using a microcontroller. In the case of slight demagnetization, the system compensates for torque reduction by increasing the current through the control strategy. In severe demagnetization conditions, the system initiates a protective shutdown to prevent further damage to the motor and drive components. In conclusion, the proposed system enhances the safety, reliability, and fault-handling capability of PMSM drives while maintaining a simple and cost-effective design, making it suitable for practical electric vehicle applications.